2016
DOI: 10.14295/2238-6416.v71i3.528
|View full text |Cite
|
Sign up to set email alerts
|

Determinação Do Teor De Sódio E Lactose Em Queijos Mussarela E Colonial Consumidos Na Região Sudoeste Do Paraná

Abstract: Pesquisas têm indicado que os queijos brasileiros têm consumido elevado teor de sal, o que pode ser visto como um problema de saúde pública, devido ao grande consumo desses produtos pela população. Além disso, poucos estudos têm avaliado o teor de lactose em queijos. Por outro lado, o lançamento no mercado de novos produtos isentos de lactose é grande. Queijos comumente apresentam baixo conteúdo de lactose, dessa forma, para alguns tipos de queijos, justifica-se o desenvolvimento de linhas de produtos com baix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
2
1
4
Order By: Relevance
“…The pH values (Figure 2A) and acidity ( Figure 2B) differed from the study by Dickel et al (2016), which reported pH from 5.62 and 5.87 and acidity expressed in lactic acid between 0.28% and 0.43% in Colonial cheeses. Sousa et al (2014) obtained pH of cheeses Development, v. 9, n. 10, e4619108590, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8590 between 5.68 and 5.18, values below the results found in this study.…”
Section: Cheeses Analysis During Maturationcontrasting
confidence: 70%
See 2 more Smart Citations
“…The pH values (Figure 2A) and acidity ( Figure 2B) differed from the study by Dickel et al (2016), which reported pH from 5.62 and 5.87 and acidity expressed in lactic acid between 0.28% and 0.43% in Colonial cheeses. Sousa et al (2014) obtained pH of cheeses Development, v. 9, n. 10, e4619108590, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.8590 between 5.68 and 5.18, values below the results found in this study.…”
Section: Cheeses Analysis During Maturationcontrasting
confidence: 70%
“…At 15 days of maturation, it can be observed that the cheeses presented 35.42 ± 0.86 g/100 g of moisture, being classified from this period as cheeses of low humidity, and it can also be named as hard cheese (Brasil, 1996) No significant change in ash content ( Figure 2E) was observed during the different maturation periods. Regarding the quantification of chlorides, the values found in the cheeses were 1.06 ± 0.1 to 1.47 ± 0.18 g/100 g, where traditional values in fresh cheeses normaly vary from 1.4 to 1.6% and Dickel et al (2016) reported averages of 1.62% to 1.81% for Colonial cheeses. These values are related to addition of calcium chloride for mass coagulation and sodium choride addition during salting.…”
Section: Cheeses Analysis During Maturationmentioning
confidence: 91%
See 1 more Smart Citation
“…Assim, o queijo coalho apresentou uma concentração de lactose 10,48 vezes maior que a ricota, e 1,83 vezes maior que o queijo minas frescal (SILVA et al, 2012). Estudo de Dickel et al (2016) encontrou teores de lactose variando de 0,19 g a 0,48 g por 100 g para os queijos mussarela e de 0,18 g a 0,36 g por 100g para os queijos coloniais. Estes resultados mostram que alguns queijos não necessitam de formulação especial para fins especiais, uma vez que alguns queijos maturados apresentam teores de lactose que permitem classifica-los como "zero lactose" ou "baixo teor de lactose" (DICKEL; JUNKES, 2016).…”
Section: A1unclassified
“…Um dos produtos derivados do leite é o queijo, definido como um produto fresco (pronto para o consumo) ou maturado (passa por um processo químico e físico), que pode ser obtido de várias formas, como pela separação parcial do soro do leite ou a partir da obtenção do coágulo do leite que nele são inseridos algumas enzimas, bactérias, podendo também serem acrescentados condimentos, aromatizantes e até mesmo substâncias alimentícias, de acordo com o Ministério da Agricultura, do Abastecimento e da Reforma Agrária (BRASIL, 1996;BRASIL, 1997;DICKEL et al, 2016).…”
Section: Introductionunclassified